End-of-Life Dreams and Visions: A Qualitative Perspective From Hospice Patients. (May 2015) - Nosek, Cheryl L.; Kerr, Christopher W.; Woodworth, Julie; Wright, Scott T.; Grant, Pei C.; Kuszczak, Sarah M.; Banas, Anne; Luczkiewicz, Debra L.; Depner, Rachel M.
End-of-life dreams and visions (ELDVs) are well documented throughout history and across cultures with impact on the dying person and their loved ones having profound meaning. Published studies on ELDVs are primarily based on surveys or interviews with clinicians or families of dead persons. This study uniquely examined patient dreams and visions from their personal perspective. This article reports the qualitative findings from dreams and visions of 63 hospice patients. Inductive content analysis was used to examine the content and subjective significance of ELDVs. Six categories emerged: comforting presence, preparing to go, watching or engaging with the deceased, loved ones waiting, distressing experiences, and unfinished business.